A cidade e a mobilidade urbana: o tecido social na relação entre o ônibus e usuários - Ferraz, Isaac Vitorio Correia (2022)
The thesis here presented addresses the issue of public transport, the bus, and its implications to users in the city of Vitória da Conquista, located in the Southwest region of Bahia. Divided into 5 chapters, this thesis begins with a general approach to the theme, without losing sight of the historical route that justifies much of the city configuration and, more specifically, of the public transport that we still have today. The methodology used was, in addition to the ethnographic field, the quantitative - questionnaire with multiple-choice questions (Survey) - and qualitative research - semistructured interviews. Undoubtedly, this research demanded an attentive listening to the territory, in order to show that urban mobility produces and reproduces the daily life of cities, explaining all forms of inequality and prejudices that are manifested. Meanwhile, we emphasize that the main objective of the research presented here is to lead readers to find alternatives, having, as starting point, the relationship between public transport and its users, in order to break with standards established since the colonization of Brazil with its history, as the need to build creative work requires creative research. Therefore, we take into account not only the indexes of the responses of bus users to the questionnaire, but also the suggestions of the interviewees, who demonstrate that the participation of the collective in solving problems pertaining to the whole population is essential, after all the aim is to maximize the possibilities. In this perspective, the research demonstrated that users of public transport are increasingly aware of their rights, which leads the government to meet the basic demands of the population, but also to go beyond, seeking to promote life quality to the inhabitants of the city in focus. This can be seen in the technological increase that the public transport sector of the city of Vitória da Conquista has gone through, verified since the beginning of the Coronavirus pandemic. In addition, one cannot lose sight of the construction of the station hub, which has brought improvements that go against the long-held idea that bus users are the people with the lowest purchasing power. Given the futuristic aspect of the station, the search for a social organization aimed at an advanced technological society is notorious. To undertake this analysis, we used the studies of David Harvey, Henri Lefebvre, Le Corbusier, Milton Santos and Raquel Rolnik about the Planned Order in urban space, among other authors, such as: Georg Simmel, Judith Butler and Michel Foucault, which were fundamental for the analysis of the relationship between subject and city and, more narrowly, between public transport and its users. Finally, with the analysis initiated here, we come to the conclusion that it is necessary to rethink the idea of city, re-signifying it and strengthening the local power, a concern that is not abstract, in view of overcoming inequalities and the absence of well-being, not to mention the rebirth of hope of those who were and continue to be victims of prejudice caused by the capitalist system in which we live